54 changing incidence and procedure complexity of coronary artery perforations. - A 10-year dataset. (4th June 2021) - Umar, Hamza; Roy, Ashwin; Oshieba, Mohammed; Ludman, Peter; Townend, Jonathan; Nadir, M. Adnan; Doshi, SN; George, Sudhakar; Zaphiriou, Alex; Khan, Sohail Q
Abstract : Background: Coronary artery perforation (CAP) is a life-threatening complication of percutaneous coronary intervention (PCI). This study aims to identify CAP predictors using contemporary data. Methods: Retrospective cohort study on all PCIs performed at the Queen Elizabeth Hospital, Birmingham between January 2010 and October 2020. Patient demographics, comorbidities, modified Ellis perforation class and perforation treatments were collected. The CAP population was split into two cohorts (1 and 2), representing the first and second 5-year period in the decade. Results: During a 10-year period, 9, 504 PCI procedures were performed with CAP occurring in 66 cases. According to the Ellis criteria, 4.5% of CAPs were type I, 13.6% type II, 45, 5% type III, and 34.8% type V. Definitive management included balloon inflation only in 27%, covered stents 20%, conservative 20%, balloon inflation with heparin reversal 12%, coronary coils 12%, heparin reversal 4.5%, emergency surgery 3%, coil and covered stent 1.5%. Overall mortality within the total perforation cohort was 14%. Emergency pericardiocentesis was required in 13 patients; in this group mortality was 46%.The difference in trends is illustrated in the table 1 . Conclusion: The data demonstrates increased incidence of CAP and mortality in the second half of the decade. This may be explained by an increase in CTO, rotablation and IVUS use (surrogates for complex PCI) and an older population with more comorbidities. Cardiac tamponade was associated with a higher mortality in those with CAP. Conflict of Interest: none